ANALISIS PENGARUH MOTIVASI, KEMAMPUAN DAN KESEMPATAN TERHADAP KINERJA DOSEN DI POLITEKNIK KESEHATAN PONTIANAK JURUSAN KEPERAWATAN DI SINGKAWANG - B11212072, PIRGONG SIREGAR (Equator Journal of Management and Entrepreneurship (EJME), 2014)
This study was conducted to determine whether the motivation, ability and opportunity to affect the performance of lecturers either partially or simultaneously at the Polytechnic of Pontianak Health Nursing Department in Singkawang. The population in this study is a Polytechnic lecturer Department of Health Nursing in Pontianak Singkawang totaling 36 people. The research method used in this study, researchers are using associative research / explanatory research with a total sample of 36 people without leadership. Analytical tool in this study is multiple linear regression. Based on the obtained partial test t value (2.272) > t table (2.040) so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. By means of motivation receipt Ha significant effect on performance, so if the motivation the better the performance level of lecturer at the Polytechnic of Health Department of Nursing in Pontianak Singkawang will rise. Based on the obtained partial test t value (5,849) > t table (2.040) so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. With the receipt of Ha means the ability of a significant effect on performance, so if the capabilities the better the performance level of the Polytechnic lecturer in the Department of Nursing in Pontianak Health Singkawang to rise. Based on the obtained partial test t value (2.200) > t table (2.040) so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. With the receipt of meaningful opportunity Ha significant effect on the performance, the better the chance that if the level of performance Polytechnic lecturer in the Department of Nursing in Pontianak Health Singkawang to rise. Based on the test results simultaneously, it can be seen that the performance of the employee calculated F value is greater than the F table (2.92) so that Ho is rejected and Ha accepted meaning simultaneously was no significant effect of independent variables (motivation, ability and opportunity) to the dependent variable (performance). Keywords : Motivation, Ability, Opportunity, Work Performance